Postnatal care. Issue 5 (May 2013) - Chatterjee, Devoshree
The role of GPs in providing maternity care has changed dramatically over the past 30 years, with a trend towards declining involvement; however, recent proposals have suggested greater involvement is required. Nevertheless, the GP remains an important point of contact for postnatal advice, and it is the GP who usually carries out the 6-week postnatal maternal check. This article aims to provide an overview of the common types of problems mothers may encounter in the postnatal period and how they can be appropriately managed. It also provides a guide for the topics to be covered during the 6-week postnatal maternal check.